Toxicity mechanisms of Cigarette Smoke on Eye and Kidney using Isolated Mitochondria: Toxicity of Cigarette Smoke on Eye and Kidney - Parvaneh Naserzadeh; Jalal Pourahmad (Iranian Journal of Pharmaceutical Sciences, 2013)
Cigarette smoking is one of the main risk factors for premature human death associated to a variety of respiratory and vascular diseases, and cancer due to containing Hundreds of toxicants. Rat mitochondria were obtained by differential ultracentrifugation and incubated with different concentrations (1, 10 and 100%) of standardized cigarette smoke extract (CSE). Our results showed that cigarette smoke extract (CSE) induced a rise in mitochondrial ROS formation and mitochondrial membrane potential decrease before mitochondrial swelling ensued in isolated eye and kidney mitochondria. Disturbance in oxidative phosphorylation was also confirmed by decrease in ATP concentration in the CSE treated mitochondria. In addition, collapse of mitochondrial membrane potential (MMP) and mitochondrial swelling caused release of cytochrome c via outer membrane rupture or MPTpore opening. Our results suggested that cigarette smoke induced toxicity in both external directly exposed and visceral tissues is the result of disruptive effect on mitochondrial respiratory chain that leads to ROS formation, lipid peroxidation, mitochondrial membrane potential decline and cytochrome c expulsion which starts apoptosis signaling and cell loss.